Matrix Assisted Laser Desorption/Ionization Mass Spectrometry Imaging (MALDI MSI) for Monitoring of Drug Response in Primary Cancer Spheroids. Issue 21 (15th October 2019) - Mittal, Parul; Price, Zoe K; Lokman, Noor A; Ricciardelli, Carmela; Oehler, Martin K; Klingler‐Hoffmann, Manuela; Hoffmann, Peter
Abstract: Malignant ascites is a fluid, which builds up in the abdomen and contains cancer cells in the form of single cells or multicellular clusters called spheroids. Malignant ascites has been observed in patients suffering from ovarian, cervical, gastric, colorectal, pancreatic, endometrial, or primary liver cancer. The spheroids are believed to play a major role in chemo resistance and metastasis of the cancer. To ease the discomfort of patients, malignant ascites (MA) is often drained from the abdomen using a procedure called paracentesis. MA retrieved via this minimal invasive procedure is a great source for cancer spheroids, which can be used for testing chemotherapeutic drugs and drug combinations. Herein, the existing workflow is adapted to make concurrent monitoring of drug accumulation, drug response, and drug metabolites feasible using primary spheroids or spheroids grown without a scaffolding matrix. To achieve this, those spheroids are embedded in matrigel, before fixing them with formalin. This makes it possible to process, store, and ship samples at room temperature. This new approach might be used to choose the best targeted therapy for each patient and thereby facilitate personalized medicine.